The role of hostile stakes in German corporate governance - Jenkinson, Tim; Ljungqvist, Alexander (Journal of Corporate Finance, 2001)
This article uses clinical evidence to show how the German system of corporate control and governance is both more active and more hostile than has previously been suggested. It provides a complete breakdown of ownership and takeover defence patterns in German listed companies and finds highly fragmented (but not dispersed) ownership in non-majority controlled firms. We document how the accumulation of hostile stakes can be used to gain control of target companies given these ownership patterns. The article also suggests an important role for banks in helping predators accumulate, and avoid the disclosure of, large stakes.